Electro-Optic Plasmonic Modulator With Direct Coupling to Silicon Waveguides - Abd Al Rahman Mohamed; Lamees A. Shahada; Mohamed A. Swillam (IEEE Photonics Journal)
A novel plasmonic Mach–Zehnder interferometer is proposed with a nonlinear polymer. Orthogonal junction coupling between silicon and plasmonic waveguides is exploited to omit the need for tapers, and in turn, reduce the footprint. An extinction ratio of about 16 dB is produced at a voltage-length product of 47 V μm. An insertion loss of 3.38 dB is achieved including the coupling to and from the silicon access waveguide. The orthogonal coupling provides wideband operation, high efficiency, low loss, and compact size for our design.